2016
DOI: 10.15666/aeer/1402_213233
|View full text |Cite
|
Sign up to set email alerts
|

Testing Plant Phenophase as Proxy: Sensitivity Analysis of First Flowering Data From the 19th Century

Abstract: Abstract. Eco-climatological studies recognise plant phenophases as high-confident climate indicators, since they are strongly dependent on heat conditions. We investigated the first flowering response of numerous plant species to inter-annual fluctuation of seasonal temperatures (e.g., heat sensitivity of the phenophase), also the rate of these species-specific sensitivities in order to test their applicability as proxy. From the few available data sources recorded in the Carpathian Basin during the 19th cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Additional historical vine and grape phenology data are available from Kecskemét (Central Hungary) from the late 17 th to the early 19 th centuries (Szabó, 1934), and from Kőszeg for the period of 1649 -1820 (Szövényi, 1965). However, neither data set has been analyzed from a climatological point of view (Kiss, 2009 (Vucetic and Vucetić, 2006) or Romania (Lehoczky et al, 2016). To fill in the many gaps in the presently available records is a major task for the future.…”
Section: Further Potentialsand Recommendationsmentioning
confidence: 99%
“…Additional historical vine and grape phenology data are available from Kecskemét (Central Hungary) from the late 17 th to the early 19 th centuries (Szabó, 1934), and from Kőszeg for the period of 1649 -1820 (Szövényi, 1965). However, neither data set has been analyzed from a climatological point of view (Kiss, 2009 (Vucetic and Vucetić, 2006) or Romania (Lehoczky et al, 2016). To fill in the many gaps in the presently available records is a major task for the future.…”
Section: Further Potentialsand Recommendationsmentioning
confidence: 99%
“…Previous research on the Carpathian Basin (Keresztes 1984, Walkovszky 1998, Schieber et al 2009, Eppich et al 2009, Molnár et al 2012, Varga et al 2012, Lehoczky et al 2016 did not follow Primack's method but still provided important data. Several previous studies (e.g., Menzel 2000, Roetzer et al 2000, Walkovszky 1998, Eppich 2009) confirmed that flowering phases advanced during the 20th century, which is connected with the increasing temperature.…”
Section: Introductionmentioning
confidence: 98%
“…Many research shows that temperature change significantly affects the life cycle of plants (e.g. Scheifinger et al 2003, Kunkel et al 2004, Hansen et al 2006, Lehoczky et al 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation